Prevalence and Predictors of Compassion Satisfaction, Burnout, and Secondary Traumatic Stress among Oncology Nurses: A Cross-sectional Survey - Ababneh, Amal Mohammad Taisir; Zeilani, Ruqayya (Journal of Posthumanism, 2025)
Background: Compassion satisfaction, burnout, and secondary traumatic stress are common experiences among oncology nurses. These issues can be investigated to better understand their sentiments and actions, early diagnosis of personal and professional suffering, and potential solutions. Objective: to assess the prevalence of compassion satisfaction, burnout, and secondary traumatic stress among oncology nurses working at university hospitals in Jordan, as well as the work-related and sociodemographic factors that influence the prevalence of the outcomes. Methodology: This study used a cross-sectional methodology to assess secondary traumatic stress, burnout, and compassion satisfaction among a purposeful sample of 176 oncology nurses. Findings: Oncology nurses reported a moderate level of professional quality of life. Results revealed a significant relationship between compassion satisfaction and nurses’ level of education. A significant relationship was observed between burnout and secondary traumatic stress. Implications: Oncology nursing policymakers should collaborate with oncology nurses and organizations to address compassion satisfaction, secondary traumatic stress, and burnout. The nursing curriculum should incorporate psychological resilience training and other psychological interventions with purpose of empowering nurses to manage their emotions and balance between work and personal life.